ANALISIS STRATEGI KINERJA KARYAWAN DI PT. COFFEE TOFFEE INDONESIA - Putriawan, Nanda Lestari; Merawati, Endang Ety; Purwoko, Bambang (SEKOLAH PASCASARJANA PRESS, 2017)
The main problem in this research is the result of the evaluation of company reports on the performance of employees has decreased from previous years and there are many complaints from employees. The purpose of this study is to analyze the performance of employees through the strategy of transformational leadership, job satisfaction and Organizational Citizenship Behavior. This study uses quantitative and qualitative research with descriptive methods. The results showed that transformational leadership and job satisfaction do not affect the performance of the employees, while the Organizational Citizenship Behavior affect employee performance. Based on the calculation of direct and indirect influence shows a comparison that leads to a more direct influence on the performance of Organizational Citizenship Behavior employee by 0.85 and the indirect effect of transformational leadership on employee performance through the mediation of Organizational Citizenship Behavior as 0.49. This indicator shows that transformational leadership will affect the performance of employees with increased Organizational Citizenship Behavior as mediation. Increase transformational leadership and Organizational Citizenship Behavior note by the management of PT. Coffee Toffee Indonesia as the company's strategy.